Association of Late Life Depression, (Non-) Modifiable Risk and Protective Factors with Dementia and Alzheimer's Disease: Literature Review on Current Evidences, Preventive Interventions and Possible Future Trends in Prevention and Treatment of Dementia - Kuo, Chih-Yun; Stachiv, Ivo; Nikolai, Tomas (International journal of environmental research and public health, 2020)
The number of people living with dementia and Alzheimer's disease is growing rapidly, making dementia one of the biggest challenges for this century. Many studies have indicated that depression plays an important role in development of dementia, including Alzheimer's disease; depression, especially, during the late life may either increase the risk of dementia or even being its prodromal stage. Despite a notably large number of carried observational studies and/or clinical trials, the association between the late life depression and dementia remains, due to the complexity of their relationship, still unclear. Moreover, during past two decades multiple other (non-)modifiable risk and possibly protective factors such as the hypertension, social engagement, obesity, level of education or physical (in)activity have been identified and their relationship with the risk for development of dementia and Alzheimer's disease has been extensively studied. It has been proposed that to understand mechanisms of dementia and Alzheimer's disease pathogeneses require their multifactorial nature represented by these multiple factors to be considered. In this review, we first summarize the recent literature findings on roles of the late life depression and the other known (non-)modifiable risk and possibly protective factors in development of dementia and Alzheimer's disease. Then, we provide evidences supporting hypotheses that (i) depressive syndromes in late life may indicate the prodromal stage of dementia (Alzheimer's disease) and, (ii) the interplay among the multiple (non-)modifiable risk and protective factors should be considered to gain a better understanding of dementia and Alzheimer's disease pathogeneses. We also discuss the evidences of recently established interventions considered to prevent or delay the prodromes of dementia and provide the prospective future directions in prevention and treatment of dementia and Alzheimer's disease using both the single-domain and multidomain interventions.
Keywords: Prospective Studies; demence; Humans; dementia; prospektivní studie; ochranné faktory; Alzheimerova nemoc; Risk Factors; testosterone; Alzheimer’s disease; apolipoprotein E; Alzheimer Disease; late life depression; Depression; substance abuse; Protective Factors; Dementia; rizikové faktory; social engagement; obesity; lidé; deprese